Research needs and methods for the use of fertilizers and soil amendments in bean-based cropping systems - Mughogho, SK; Wortmann, Charles S. (Southern Africa Development Coordination Conference (SADCC), 1988)
Bean yields are expected to increase due to improved varieties and better cultural and harvesting practices. Higher yields increase the nutrient requirements of the bean crops and the complexity of management. Better low input management practices will be needed for beans grown in pure stand and in multiple cropping systems. Research in bean growing countries of Africa should not only concentrate on the use of soluble fertilizers to solve nutrient deficiency problems, but also investigate ways of improving the availability of native and applied soil nutrients. Phosphorus deficiency problems should be studied together with those of aluminum toxicity. Efforts should continue to improve the efficiency of use of P fertilizers and phosphate rock. When P is being applied to soils at high rates, the relationship of P to other soil nutrients, especially zinc, becomes more important. Nitrogen needs to better managed to meet the needs of the component crop without inhibiting N fixation by the bean crop. The management of applied nitrogen, phosphorus and other nutrients needs further research for beans grown in association with other crops to increase the yield of all component crops and to provide an adequate "sink" to stimulate nitrogen fixation. The ultimate goal of fertilizer research is to develop superior soil fertility management practices. The viability of the alternatives is dependent on how they affect the productivity of the system, but also on how they affect the stability and profitability of the system. Economic analysis of the profitability and stability of alternative practices should be a part of the research process. (AS)